International Lesbian and Gay Association : boletin informativo para America Latina. (Guadalajara : GOHL, 1988)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie : GOHL, Apartado Postal 1-1693, 44100 Guadalajara Jal. [Mexico]
Spaans
Periodiek